Critical Discourse Analysis of RT news headlines on Venezuela’s post-coup crisis in 2019-2020 - Ihor Matselyukh (LingBaW)
This article researches the biased content of the propagandistic channel RT through the prism of Critical Discourse Analysis (CDA). It attempts to uncover the linguistic means of creating biased content in RT headlines that cover the Venezuela’s post-coup crisis of 2019-2020. It offers a CDA approach to the systemic bias in the headlines of 375 news stories featured on one of the most tendentious webcasters, the Russian state news provider RT. The current CDA focuses on presuppositions and implicatures, back- and fore-grounding, agency, lexis, punctuation, and briefly on other figurative linguistic means in the headlines and traces their relative recurrence that might form a pattern.